D:L-Amino Acid Modeling Reveals Fast Microbial Turnover of Days to Months in the Subsurface Hydrothermal Sediment of Guaymas Basin - Møller, Mikkel H.; Glombitza, Clemens; Lever, Mark A.; Deng, Longhui; Morono, Yuki; Inagaki, Fumio; Doll, Mechthild; Su, Chin-chia; Lomstein, Bente A. (Frontiers in Microbiology, 2018)
We investigated the impact of temperature on the microbial turnover of organic matter (OM) in a hydrothermal vent system in Guaymas Basin, by calculating microbial bio- and necromass turnover times based on the culture-independent D:L-amino acid model. Sediments were recovered from two stations near hydrothermal mounds (<74°C) and from one cold station (<9°C). Cell abundance at the two hydrothermal stations dropped from 108 to 106 cells cm-3 within 5 m of sediment depth resulting in a 100-fold lower cell number at this depth than at the cold site where numbers remained constant at 108 cells cm-3 throughout the recovered sediment. There were strong indications that the drop in cell abundance was controlled by decreasing OM quality. The quality of the sedimentary OM was determined by the diagenetic indicators %TAAC (percentage of total organic carbon present as amino acid carbon), %TAAN (percentage of total nitrogen present as amino acid nitrogen), aspartic acid:β-alanine ratios, and glutamic acid:γ-amino butyric acid ratios. All parameters indicated that the OM became progressively degraded with increasing sediment depth, and the OM in the hydrothermal sediment was more degraded than in the uniformly cold sediment. Nonetheless, the small community of microorganism in the hydrothermal sediment demonstrated short turnover times. The modelled turnover times of microbial bio- and necromass in the hydrothermal sediments were notably faster (biomass: days to months; necromass: up to a few hundred years) than in the cold sediments (biomass: tens of years; necromass: thousands of years), suggesting that temperature has a significant influence on the microbial turnover rates. We suggest that short biomass turnover times are necessary for maintance of essential cell funtions and to overcome potential damage caused by the increased temperature.The reduced OM quality at the hyrothemal sites might thus only allow for a small population size of microorganisms.